The effect of external wings on the behavior of suction anchor - Monajemi, H.; Abdul Razak, H. (2008)
Suction anchors may be subjected to quasihorizontal, quasivertical or inclined loading depending on the type of structure and the water depth. The loading conditions can give rise to horizontal and vertical loads, and moments. To achieve the best performance, suction anchors may be used in different ways. A single cylindrical unit is normally used for typical floaters, and to achieve higher load resistance a cluster of several attached cylinders may be installed. They may also be used with external wings to optimize the horizontal holding capacity by an enlarged projected area. The behaviour of the suction anchor subjected to lateral and pullout loading is presented in this paper. This is to observe the effects of the external wings on the failure mechanism and ultimate capacity of the foundation. The general-purpose finite element program DIANA is being used for this study. A nonlinear analysis was performed on a three dimensional model formed using eight-node isoparametric solid brick elements. The soil was modelled as an elastic perfectly plastic material with von Mises yield criterion for saturated clay. Both load control and displacement control analyses were used for this study.